Empowering financial well-being through life skills: enhancing the economic resilience of B40 households in Malaysia - Sabri, Mohamad Fazli; Ahmad Suhaimi, Siti Shazwani; Nazuri, Nur Shuhamin; Law, Siong Hook; Magli, Amirah Shazana (Universiti Putra Malaysia, 2025)
In 2020, the B40 group in Malaysia, comprising around 2.7 million households earning less than RM 4,850 (US$1,045) per month, faced significant economic and social challenges. Key issues include limited access to education, healthcare, affordable housing, and rising living costs. Financial management is crucial for this group to achieve stability and well-being. This study explores the relationship between financial knowledge, locus of control, financial behaviour, life skills, and the financial well-being of B40 households. Data was collected through a cross-sectional study from 1,948 B40 households in five states across Peninsular Malaysia, Sabah, and Sarawak using cluster sampling. SEM-PLS analysis revealed a strong positive relationship between financial knowledge, locus of control, and financial well-being. Additionally, financial behaviour was found to mediate the link between financial knowledge, locus of control, and financial well-being. Life skills further moderated these relationships, emphasizing their importance in improving financial outcomes. The findings contribute to the theoretical understanding of financial well-being and provide actionable insights for policymakers and organizations to design programs aimed at enhancing the financial resilience of B40 households in Malaysia.